Dampak Efektivitas Pemberian Ekoenzim Sebagai Agen Pertumbuhan dan Penambah Nutrisi Tanaman pada Berbagai Jenis Tanaman Budidaya di Indonesia - Wulan, Indah Retno; Tanjung, Jeane Claudea; Sinatrya, Azka; Fahima, Sahidatun; Ngadisih, Ngadisih; Lestari, Prieskarinda (Universitas Tanjungpura, 2024)
Sustainable agriculture is one of the latest innovations in the agricultural sector. This should consider the importance of environmental sustainability in its application in agriculture to prevent and minimize land damage and environmental pollution. One of the main pollution cases on agricultural land is the excessive use of chemical fertilizers to promote and maintain plant growth. Besides, providing plant nutrition can be done with the presence of ecoenzymes. Ecoenzymes are the result of complex fermentation of organic waste which can be used as plant growth and nutrient enhancers. This review study aimed to examine the effectiveness impact of providing ecoenzymes on various cultivated plants in Indonesia. Based on the results of the review, the ecoenzymes can help the growth of horticultural, ornamental, food, and annual plants which are also influenced by various characteristic factors, plant type, and concentration dose. Dosing ecoenzymes also depends on the use of additional fertilizer during the planting period.